Kerendahan Hati dan Kepedulian Lingkungan: Filipi 2:3-4 Mengatasi Perilaku Membuang Sampah Sembarangan: "Humility and Environmental Care: Philippians 2:3-4 Overcoming Littering" - Marpaung, Andre; Anton Arifandi; Eri (SCRIPTA: Jurnal Teologi dan Pelayanan Kontekstual, 2024)
The purpose of this study is to identify Philippians 2:3-4 as the basis for one's understanding of the importance of caring for others with full devotion. Because the current waste problem is a problem that must be solved. However, the awareness of every policy regarding the dangers of waste is the main problem. For this reason, this article provides an effort to provide awareness about the importance of awareness and concern for this increasingly degraded environment. Philippians 2:3-4 is an example of counsel for all walks of life, where Paul is present to enlighten the Philippians about the importance of caring for others. The anthropocentric nature must be immediately eliminated in the life of mankind. In writing this article, the author uses a library study (library reaserch) by adding the results of interviews as a primary source of their responses to various problems caused by indifference to the environment. So it was found that in this waste problem, a person's selfish attitude, and indifference to the dangers that can occur if they throw garbage carelessly. An attitude of concern for others and the environment is very important to maintain a balance in life.